BRANDING KOPI TULI DALAM MEMBANGUN BRAND IDENTITY - Sungkono, Nono; Hamzah, Radja Erland; Toruan, Rialdo Rezeky Manogari Lumban; Tryarno, Adi Nur Achmad (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2022)
Branding strategy is a step to achieve goals that function in regulating all brand elements related to consumer attitudes and behavior. As in Kopi Tuli, carrying out a branding strategy with its limitations, namely the deaf disability, with the limitations that Kopi Tuli has as a deaf disability, it is possible that Kopi Tuli can carry out a branding strategy aimed at managing all brand elements, and building brand identity. This study aims to determine the branding Kopi Tuli, to determine brand identity Kopi Tuli, and to determine the branding Kopi Tuli in building a brand identity. Using the concept of branding put forward by experts, namely Brand identity, Brand positioning, Brand communication, Brand personality, and Brand equity. And to find out the identity of Kopi Tuli, Aaker's brand identity model divides brand identity into twelve dimensions into four perspectives. Besides that, to find out the branding Kopi Tuli brand identity using the research results that have been described. This study uses a qualitative descriptive method by conducting direct observations and interviews with the founders of Kopi Tuli, consumers of Kopi Tuli and advertising experts. The results showed that the branding through social media Instagram was by promoting products and learning sign language. brand identity Tuli shows that Kopi Tuli builds brand and quality products that have their own distinctive taste.strategy branding in building brand identity has communication barriers, to overcome this, the deaf coffee uses sign language through social media Instagram and events, aiming to build a deaf coffee brand identity and products.